tag:blogger.com,1999:blog-79194806162064142442017-09-01T04:10:13.211+01:00Sean's BlogThese are the whimsical thoughts that I shall be having during my times at university...Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.comBlogger9125tag:blogger.com,1999:blog-7919480616206414244.post-6627748097691558962011-02-23T00:08:00.000+00:002011-02-23T00:08:27.706+00:00Give this one a try...<span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;">“A vagrant who stole three melons weighing three pounds each, came to a bridge which was just strong enough to hold him and six pounds. Without throwing any of the melons across the bridge, how did the vagrant cross the bridge with the melons, none of which touched the bridge?”</span>Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com0tag:blogger.com,1999:blog-7919480616206414244.post-16511606493883689072011-02-20T17:32:00.002+00:002011-02-20T17:32:29.824+00:00The Answer!!!!!<span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;">How can you put 10 lumps of sugar into three cups so there is an odd number of lumps in each cup?</span><br /><span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;"><br /></span><br /><span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;"><br /></span><br /><span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;"><br /></span><br /><span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;"><span class="Apple-style-span" style="line-height: normal;"></span></span><br /><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;">Put five lumps in the first cup, two in the second, and three in the third.</div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;">Then sit the third cup in the second cup.</div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><br /></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><br /></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;">:D :D :D :D :D</div>Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com2tag:blogger.com,1999:blog-7919480616206414244.post-47143201442079553492011-02-17T00:08:00.000+00:002011-02-17T00:08:17.466+00:00More maths!!!Its been a while since I've posted on here - the dissertation is really dragging me down, plus I went away to snowdon for a weekend's climbing :D<br /><br />Heres a quick one today, promise ill put a better one up next time :D<br /><br /><br /><span class="Apple-style-span" style="color: #222222; font-family: Georgia, 'Times New Roman', Times, serif; font-size: 14px; line-height: 25px;">How can you put 10 lumps of sugar into three cups so there is an odd number of lumps in each cup?</span>Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com4tag:blogger.com,1999:blog-7919480616206414244.post-6232246654120963932011-02-01T11:52:00.001+00:002011-02-01T11:52:58.749+00:00The Answer!!!I'm sure a lot of you are going to be annoyed by this.... but it is just a simple case of where common sense is wrong :)<br /><br /><br /><br /><strong>I have two children, and at least one of them is a son. What is the probability that the other is also a son?</strong><br /><br /><br /><br />If I have only one child, the probability is $\frac{1}{2}$ that it’s a boy.<br /><br /><br />But if I have two children, there are really four possibilities, depending on birth order: boy-boy, boy-girl, girl-boy, girl-girl. You know that at least one child is a boy, so you can exclude the girl-girl option. Of the three that remain, only one has two boys. So the probability that my other child is a boy is $\frac{1}{3}$.<br /><br /><br />Ta-dah!Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com6tag:blogger.com,1999:blog-7919480616206414244.post-34238097779066343662011-01-31T00:12:00.001+00:002011-01-31T00:23:51.423+00:00As you enjoyed my last piece of maths...<span class="Apple-style-span" style="font-family: inherit;">Well hello to all my new followers! Hope you like $\LaTeX{}$ as i'm particularly fond of it and so you will see it all over my blog. My exams are finally over for this semester, and as a treat, I am going to show you another question I had to answer! However its too late tonight and I have a 9am tomorrow..... So heres a question to keep you all intrigued...</span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="color: #222222; line-height: 25px;"><span class="Apple-style-span" style="font-family: inherit;">I have two children, and at least one of them is a son. What is the probability that the other is also a son?</span></span>Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com14tag:blogger.com,1999:blog-7919480616206414244.post-86519672948261098462011-01-23T01:30:00.004+00:002011-01-23T02:13:26.810+00:00One side of hand-written notes only...It's finally over! My week of dreaded exams... Not that they went to plan. Now with most exams, it is normally customary for the paper to be proof read, i.e before the actual exam is sat. Well that certainly does NOT seem to be the case with the folks here at the University of Portsmouth! Thats right, we were due to sit our exam at 11:15 on a Thursday... At 11:16 - I raised my hand with a puzzled look on my face.<br />'I'm afraid theres a mistake with the paper'<br />Looking through, every symbol had been replaced with a black dot. Every bracket, $\pi$, $\rho$, $\Omega$,.. well you get the idea. What with this being an exam on astrophysics, those symbols are pretty much used through out, and so the whole exam was a write off. after half an hour, it was finally decided that the exam would be cancelled, and so we all had to leave one at a time (as there were still exams happening) which took another 10 minutes. It was finally decided that another exam would be held tomorrow (the Friday).<br /><br />After we vented our rage upon the Head of Department, and various other people, we eventually managed to sit our exam. As I went to the trouble of learning it so much, I'm actually going to include one of the questions I had to answer in this blog, and I'll also show the sheet of notes I took in... (the blog title is a clue).<br /><br /><span class="Apple-style-span" style="font-family: Verdana, sans-serif;">1) Show that a sphere of uniform density will collapse to zero radius in a "free-fall" time of</span><br /><span class="Apple-style-span" style="font-family: Verdana, sans-serif;">\[t_{FF} = \left[\frac{3\pi}{32G\rho}\right ] ^{\frac{1}{2}}\]</span><br /><span class="Apple-style-span" style="font-family: Verdana, sans-serif;"><br /></span><br /><br /><br /><br /><span class="Apple-style-span" style="font-size: x-large;">We</span> <span class="Apple-style-span" style="font-size: large;">can </span>start solving this by stating the following formula:<br />\[\rho\frac{d^{2}r}{dt^{2}}=-\frac{GM}{r^{2}}\rho-\frac{dP}{dr}\]<br /><br />We are told in the question that we are working in uniform density. As of that, $\rho$ can be 'ignored' as it is a constant. WE also know that we are in free-fall, so $P=0$. That leaves us with the following:<br />\[\frac{d^{2}r}{dt^{2}}=-\frac{GM}{r^{2}}\]<br />We can start by multiplying through by $\frac{dr}{dt}$, to give:<br /><br />\[\frac{dr}{dt}\left(\frac{d^{2}r}{dt^{2}\right)}=-\frac{GM}{r^{2}}\frac{dr}{dt}\]<br /><br />We can integrate both sides of this equation with respect to $t$, however before we do that, it is possible to make some substitutions on the Left hand side.<br />\[x=\frac{dr}{dt}\]<br />\[\frac{dx}{dt}=\frac{d^{2}r}{dt^{2}}\]<br /><br />We can now re-write as:<br /><br />\[\int x\left(\frac{dx}{dt}\right)dt=- \int \frac{GM}{r^{2}}\left(\frac{dr}{dt}\right)dt\]<br /><br />We can cancel the $dt's$ on both sides of the equation, which leaves us with:<br /><br />\[\int x dx=- \int \frac{GM}{r^{2}}dr\]<br /><br />\[\Rightarrow\frac{x^{2}}{2}=\frac{GM}{r}+c\]<br /><br />We can state that when $t=0, r=r_{0}$, where $r_{0}$ is the starting radius. We stated above that $x=\frac{dr}{dt}$, and so now $t=0$, we can rewrite the above formula to show that:<br /><br />\[c=-\frac{GM}{r_{0}}\]<br /><br />\[\therefore \frac{x^{2}}{2}=\frac{GM}{r}-\frac{GM}{r_{0}}\]<br /><br />\[\Rightarrow x^{2}=\frac{2GM}{r}-\frac{2GM}{r_{0}}\]<br /><br />\[\Rightarrow \left(\frac{dr}{dt}\right)^{2}=\frac{2GM}{r}-\frac{2GM}{r_{0}}\]<br /><br />Now we need to integrate, with $t=t_{FF}$, and $r=0$<br /><br />\[t_{FF}\Rightarrow \int_0^{t_{FF}} dt= \int_{r_{0}}^0 \left(\frac{dt}{dr}\right)dr\]<br /><br />By inversing the right hand side, we can show that<br />\[\int_{r_{0}}^0 \left(\frac{dr}{dt}\right)^{-1}dr\]<br /><br /> Now we are basically going to perform some shuffling about with the equations, which involves square-rooting $\frac{dr}{dt}$, and then inversing. This can be shown:<br /><br />\[\left(\frac{dr}{dt}\right)^{2}=\frac{2GM}{r}-\frac{2GM}{r_{0}}\Rightarrow \frac{dr}{\sqrt{\frac{2GM}{r}-\frac{2GM}{r_{0}}}}=dt\]<br /><br />We can no integrate this, though we can take out some constants to make life a bit easier.<br />Take out:<br />\[-\frac{1}{\sqrt{2GM}}\]<br />To give<br />\[-\frac{1}{\sqrt{2GM}}\int_{r_{0}}^0 \left(\frac{r}{1-\frac{r}{r_{0}}}\right)^{\frac{1}{2}}dr\]<br /><br />We can now introduce some more variables in which we can sub in:<br />\[r=r_{0}\sin^{2}\theta\]<br />\[dr=2r_{0}\cos\theta\sin\theta d\theta\]<br /><br />If we substite $r$ into $\left(\frac{r}{1-\frac{r}{r_{0}}}\right)$, we get the following:<br />\[\left(\frac{r}{1-\frac{r}{r_{0}}}\right) \Rightarrow\left(\frac{r_{0}\sin^{2}\theta}{1-\sin^{2}\theta}\right)=\left(\frac{r_{0}\sin^{2}\theta}{\cos^{2}\theta}\right)=\sqrt{r_{0}}\tan\theta\]<br /><br />Now that has been simplified we can substitute our new values into the intergral, which gives us the following:<br /><br />\[t_{FF}=-\frac{1}{\sqrt{2GM}}\int_{r_{0}}^0\left(2r_{0}\cos\theta\sin\theta\sqrt{r_{0}}\tan\theta d\theta\]<br /><br />this can be simplified further by saying:<br />\[2r_{0}\times r_{0}^{\frac{1}{2}}=2r_{0}^{\frac{3}{2}}\]<br />and<br />\[\tan\theta\times\cos\theta\times\sin\theta=\sin^{2}\theta\]<br />\[\sin^{2}\theta=\frac{1-\cos 2\theta}{2}\]<br /><br />We can take out from the intergral that $2r_{0}^{\frac{3}{2}}$ is a constant, leaving us with:<br /><br />\[-\frac{2r_{0}^{3}}{\sqrt{2GM}}\int_{r_{0}}^0\frac{1}{2}\left(1-\cos 2\theta\right)d\theta\]<br /><br />so when $r=r_{0}$, $\sin^{2}\theta=1\Rightarrow\theta=\frac{\pi}{2}$<br /><br />\[\therefore =-\frac{2r_{0}^{3}}{\sqrt{2GM}}\left[\frac{1}{2}\theta-\frac{1}{4}\sin2\theta\right]_{2\pi}^{0}\]<br /><br />As we know both of the limits would cancel out $\sin$, we can cancel through on the second half of the intergral, which we then get left with:<br /><br />\[\frac{\pi}{4}\left(\frac{-2r_{0}^{3}}{GM}\right)^\frac{1}{2}\]<br /><br />Once again stating formula, we can say that:<br /><br />\[M=\frac{4}{3}\pi r_{0}^{3}\rho\]<br /><br />We can substitute that into above to give:<br /><br />\[\frac{\pi}{4}\left( \frac{-2r_{0}^{3}}{{G\left(\frac{4}{3}\pi r_{0}^{3}\rho}}\right)}\right)^{\frac{1}{2}}\]<br /><br />This is where the magic happens - you can see that the $r_{0}^{3}$'s can cancel out, we can take the $\frac{\pi}{4}$ into the square root section by squaring (and then we can cancel the bottom $\pi$, giving:<br /><br />\[\left(\frac{-2\pi}{16G{\frac{4}{3}}\rho}\right)\]<br /><br />taking the $3$ upto the top, and then dividing through by $2$ can give:<br /><br />\[\left(\frac{3\pi}{32G\rho}\right)^{\frac{1}{2}}\]<br /><br />Which is what we were after!Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com16tag:blogger.com,1999:blog-7919480616206414244.post-73202946831618683142011-01-14T23:20:00.000+00:002011-01-14T23:20:09.535+00:00A lovely little Question I Like<span class="Apple-style-span" style="font-family: inherit;">Well its been a quite time on here, that can only mean it's exam time. As i'm in final year I've been taking it full force - university at 10 am every morning, decent breakfast, the whole 9 yards. the best part is that I feel great!. As I have been revising, that unfortunatly means nothing of interest will occur. Although Next weekend (22$^{nd}$ of January) should be interesting...</span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="font-family: inherit;">In the meantime, here is one of my favourite simple maths questions, that I find really enjoyable. </span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="font-family: inherit;">A Curious Exchange.</span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="line-height: 25px;">Mrs. Smith: The product of their ages is 36, and the sum of their ages is the address on our door here.</span><br /><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">Census Taker: (after some figuring) I’m afraid I can’t determine their ages from that …</span></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">Mrs. Smith: My eldest daughter has red hair.</span></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">Census Taker: Oh, thanks, now I know.</span></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">How old are the three girls?</span></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;">If this were a blog that people actually read and commented on, then I would have probably delayed the answer for a while, however as I am probably the only one to read this, I shall give the answer below. </div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">I would like to hope that people would at least attempt this though.</span></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;">Its easier than you think. </div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><br /><span class="Apple-style-span" style="font-family: inherit;">So analysing the question, we are told "The product of their ages is 36"</span><br />So we can say that we need 3 numbers that have the product of 36.<br />1 - 1 - 36<br /><span class="Apple-style-span" style="font-family: inherit;">1 - 2 - 18</span><br /><span class="Apple-style-span" style="font-family: inherit;">1 - 3 - 12</span><br /><span class="Apple-style-span" style="font-family: inherit;">1 - 4 - 9</span><br /><span class="Apple-style-span" style="font-family: inherit;">1 - 6 - 6</span><br /><span class="Apple-style-span" style="font-family: inherit;">2 - 2 - 9</span><br /><span class="Apple-style-span" style="font-family: inherit;">2 - 3 - 6</span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="font-family: inherit;">Now we have this list, we then analyse the second part of what we are told. " and the sum of their ages is the address on our door here"</span><br /><span class="Apple-style-span" style="font-family: inherit;">Now we take the sum of all these:</span><br /><br /></div><div style="line-height: 25px; margin-bottom: 10px; margin-left: 0px; margin-right: 0px; margin-top: 0px; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px;"><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">1 - 1 - 36 = 38</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">1 - 2 - 18 = 21</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">1 - 3 - 12 = 16</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">1 - 4 - 9 = 14</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">1 - 6 - 6 = 13</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">2 - 2 - 9 = 13</span></div><div style="margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px;"><span class="Apple-style-span" style="font-family: inherit;">2 - 3 - 6 = 11</span></div></div><span class="Apple-style-span" style="font-family: inherit;"><br /></span><br /><span class="Apple-style-span" style="font-family: inherit;">We can see that 2 of the groups of numbers sum to 13. We now no that the ages of the 3 daughters are either (1, 6, 6) or (2, 2, 9).</span><br />Like the census taker in the question, we cannot yet work out who the ages, however what we are told next makes that possible. "<span class="Apple-style-span" style="line-height: 25px;">My eldest daughter has red hair"</span><br /><span class="Apple-style-span" style="font-family: inherit; line-height: 25px;">As a 'Red' herring, we can finally say that the age of the daughters are 2, 2, and 9. This is as we know that there is an eldest daughter, so we can eliminate the other set of numbers.</span><br /><span class="Apple-style-span" style="font-family: inherit; line-height: 25px;"><br /></span><br /><span class="Apple-style-span" style="font-family: inherit; line-height: 25px;">Isnt it nice?</span><br /><span class="Apple-style-span" style="font-family: inherit;"><br /></span>Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com1tag:blogger.com,1999:blog-7919480616206414244.post-54025976491505715832010-12-28T21:18:00.000+00:002010-12-28T21:18:23.554+00:00Just because I can...So now I have $\LaTeX{}$ fully up and running and function able, I thought I would start by saying why I have decided to actually bother getting it working. Being a mathematics student in my final year, I have to complete a 'final year project' (Dissertation or Thesis to anyone else), and as with most scientific papers, the form they are presented in is indeed $\LaTeX{}$. My final year project is going to be based upon statistical forecasting, and the software that is used within (but you shall hear more about this in another post).<br />For now I'm going to spend the rest of this post with a nice bit of proof showing how we get the quadratic equation from.<br /><br />If you look online there are many long winded ways of showing proof for this formula. Most take up a page and can be quite hard to follow: I prefer this method.<br />Like with most quadratic formulas, we start with the basic idea that \[ax^{2}+bx+c=0\] From here, we can start by multiplying through by $4a$ <s><span class="Apple-style-span" style="font-size: xx-small;">(You just do, ok?)</span></s>, which would give us something like this: \[4a^{2}x^{2}+4abx+4ac\]With a little magic, which I like to call completing the square, we can now tidy up $4a^{2}x^{2}+4abx$ to make a much nicer \[\left(2ax+b \right)^{2}-b^{2}\]<br />So now we have an equation that looks a little something like this: \[\left(2ax+b \right)^{2}-b^{2}+4ac=0\]<br />Taking $-b^{2}+4ac$ over to the other side, then square rooting leaves us with:\[2ax+b=\pm\left(b^{2}-4ac\right)\] Now all that is left to do is minus the $b$ and divide through by the $2a$, leaving us with the oh so lovely: \[x=\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}\]<br />BeautifulSean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com2tag:blogger.com,1999:blog-7919480616206414244.post-44690077454830756162010-12-28T18:32:00.007+00:002010-12-28T18:58:33.775+00:00Welcome BackWell after conclusive Testing I have managed to get $\LaTeX{}$ working in my blog! For the new year I shall start publishing more about the work I am doing as well as other going's on.<br />\[\frac{2}{3}\]<br /><br />Doesn't that look nice?Sean Canninghttp://www.blogger.com/profile/11137178073178545561noreply@blogger.com0